Reference and identity in Jewish, Christian, and Muslim scriptures the same god? - Buckner, D. E. (Philosophy of language, 2020)
This book proposes a theory of reference--answering the question of whether Jewish, Christian, and Muslim scriptures refer to the same God--within a semantic framework acceptable to atheists and fideists.